Cara Pemupukan yang Menguntungkan Usaha Tani Kentang di Kabupaten Banjarnegara, Jawa Tengah - Dewi Sahara; Munir Eti Wulanjari (Institut Pertanian Bogor, 2022)
Potatoes are one of the horticultural commodities with high economic value and have the opportunity to fill the domestic and export markets. However, potato productivity in Central Java tends to decline due to suboptimal fertilization technology. This study aims to assess crop growth, potato production, and the economic feasibility of potato farming. The experiment was carried out in Sumberejo Village, Batur District, Banjarnegara Regency, in September-December 2021 with a pilot demonstration plot covering an area of 0.4 ha by applying dibbling and spreading fertilization. Data on plant growth and production were analyzed using average values and t-tests‒; input-output data were analyzed financially to calculate economic feasibility. The results showed that the dibbling method had an insignificant effect on the vegetative and generative plant growth, but potato production by dibbling was about 3 kg ha-1 compared to production by dispersing. The dibbling method gave a higher profit memberikan nilai keuntungan lebih tinggi with B/C = 0.81 compared to the dispersed method with B/C = 0.68. The change in fertilization from spread to dibble gave high benefits with an indication of MBCR = 8.11. If there is a decrease in production and prices, then fertilization by dibbling has a higher tolerance limit (44.87%) to the losses caused than dibbling fertilization, which has a tolerance limit of 40.49%. Keywords: fertilization methods, economic feasibility, potato, profits, production